Anti-brain Cancer Activity of New (N, O) Bidentate Schiff Base Ligand and its Metal Ion Complexes - Hayder Muneam A.M. (Journal of Global Pharma Technology, 2016)
Anti-brain cancer activity was studied by treated it with new bidentate Schiff base ligand and its metal ion complexes. The ligand 2-(((Z)-1-(4-(((E)-4-(dimethyl amino) benzylidene) amino) phenyl) ethylidene) amino) phenol and its metal ion complexes have been characterized by using FT-IR, UV. visable, 1H-NMR,13C-NMR, mass spectroscopy, thermal analysis, (CHN) analysis, atomic absorption, magnetic susceptibility and molar conductivity. The octahedral geometry was suggested for all the synthesized complexes with the bidentate ligand in (1:2) mole ratio of metal: ligand. The M (II) complexes were having neutral nature while the Fe(III) was an electrical according to the magnetic susceptibility. Copper ion complex has been shown a good anti-brain cancer activity than other complexes and the ligand.Keywords: Schiff base, Anti-brain cancer, Metal ion complexes, Bidentate ligand.